2023
DOI: 10.2174/1573403x18666220818155039
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy and COVID-19: A Case Report and Literature Review

Abstract: Bckground: Takotsubo cardiomyopathy is characterized by transient regional ventricular abnormalities in the absence of coronary artery disease and is reported as a complication of COVID-19. Case Representation: It can have a diverse clinical presentation, occasionally resembling an acute coronary syndrome, and progress to acute heart failure and cardiogenic shock with an adverse effect on patients' prognosis. A high index of suspicion and a thorough diagnostic approach supported by ancillary studies like ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…José et al conducted a literature review and identified 71 subjects with TTS and COVID-19 across 35 published reports, in which 18.3% of patients died. 41 Another systematic analysis, which included 52 TTS cases from a total of 40 articles, reported an all-cause mortality rate of 36.5% in TTS patients with COVID-19. 42 Additionally, the European Association of Cardiovascular Imaging found that 2% of 1216 COVID-19 patients included in their analysis had concomitant diagnoses of TTS based on echocardiography findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…José et al conducted a literature review and identified 71 subjects with TTS and COVID-19 across 35 published reports, in which 18.3% of patients died. 41 Another systematic analysis, which included 52 TTS cases from a total of 40 articles, reported an all-cause mortality rate of 36.5% in TTS patients with COVID-19. 42 Additionally, the European Association of Cardiovascular Imaging found that 2% of 1216 COVID-19 patients included in their analysis had concomitant diagnoses of TTS based on echocardiography findings.…”
Section: Discussionmentioning
confidence: 99%
“…José et al . conducted a literature review and identified 71 subjects with TTS and COVID‐19 across 35 published reports, in which 18.3% of patients died 41 . Another systematic analysis, which included 52 TTS cases from a total of 40 articles, reported an all‐cause mortality rate of 36.5% in TTS patients with COVID‐19 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, TTS may typically manifest as chest pain (38%) associated with respiratory symptoms, but in few cases with cardiac symptoms only (7.7%). Cardiac troponins are often elevated (>80%) and, notably, in-hospital mortality is high (18%-19%) (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Whether TTS was due to the SARS-CoV-2 infection or due to SARS-CoV-2 vaccination was not discussed. Since both occurred before the suspected onset of TTS and both have been reported as causes of TTS, 2 , 3 it is crucial to delineate whether one or both were causative. It also should be considered whether TTS was triggered by respiratory insufficiency (there was severe hypoxigenation), which can cause severe anxiety, and whether TTS occurred prior to hospitalization or prior to S ARS-CoV-2 vaccination.…”
mentioning
confidence: 99%